Study on the impacts of the U.S. financial crisis on stock markets in Asia - Rim, Hong; Setaputra, Robert; Rosle Mohidin (JW Press, 2012)
The impacts of the U.S. financial crisis (2008) on Asian stock markets have been examined by using daily returns of 10 (ASEAN, non-ASEAN) stock market indexes. Some notable findings from the vector auto-regressive model are: 1) the U.S. crisis had no significant impacts on Asian markets; 2) the U.S. financial market became less dominant in Asian markets; 3) the speed of adjustment slightly increased in most Asian markets; 4) the U.S. market became less integrated with Asian markets during the U.S. crisis (i.e., much diversification benefits to be exploited in Asian markets); and 5) there were observed strong spillover effects from the U.S. market to Asian markets for the whole period. The strong volatility spillovers suggest significant negative impacts from the U.S. market to financial markets in Asia.